2007
DOI: 10.1021/ja0727518
|View full text |Cite
|
Sign up to set email alerts
|

Additive-Free Synthesis of Poly(phenylene oxide):  Aerobic Oxidative Polymerization in a Base-Condensed Dendrimer Capsule

Abstract: The additive-free synthesis of poly(phenylene oxides) by aerobic oxidation was achieved using a copper complex in a dendritic phenylazomethine structure. The outer shell composed of Schiff base units assists the catalytic function of the inner Cu complex moiety. It is important that the hybrid structure should be designed with a rigid architecture not to deactivate the catalytic center. Due to the rigid π-conjugating structure of the phenylazomethine dendrimer, the metal center can retain its fine conformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 19 publications
2
28
0
Order By: Relevance
“…As shown for a previously reported [CuCl 2 A C H T U N G T R E N N U N G (imine) 2 ] complex with square-planar coordination, [22] the assembly was Figure 6. a) Image (5 mm 5 mm) of C12DPAG3-G2 from tapping-mode AFM on mica prepared from a dendrimer solution (20 mg mL À1 ) in heptane, and b) proposed assembly structure of C12DPAG3-G2 using 3D models.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…As shown for a previously reported [CuCl 2 A C H T U N G T R E N N U N G (imine) 2 ] complex with square-planar coordination, [22] the assembly was Figure 6. a) Image (5 mm 5 mm) of C12DPAG3-G2 from tapping-mode AFM on mica prepared from a dendrimer solution (20 mg mL À1 ) in heptane, and b) proposed assembly structure of C12DPAG3-G2 using 3D models.…”
supporting
confidence: 64%
“…Previously, our group reported the application of a copper/DPA complex as an effective catalysis. [22] Copper complexes are often used for building supramolecular structures with square-type coordination. We confirmed the complexation behavior of C12DPAG3-G2 and C12DPAG3er with CuCl 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that only a very low concentration of the Cu(II)-PVI-24.7 complex was required to retain the relatively high PPO yield, and the catalytic efficiency of the Cu(II)-PVI-24.7 complex was nearly 10 times higher than that of the Cu(II)-EDTA complex. The significant enhancement in the catalytic efficiency may have been due to the concentration effect mentioned by Yamamoto et al, 24 which is discussed in detail later.…”
Section: Effect Of the Cu(ii)-pvi Complex Concentration On The Oxidatmentioning
confidence: 93%
“…[5,6] In a previous communication, we reported that a minimum amount of the copper complex with a dendritic phenylazomethine (DPA) ligand effectively oxidized F 2 PhOH to afford poly(2,6-difluorophenylene oxide) (F 2 PPO). [7] Dendrimer architecture has attracted much attention as a platform for catalysts [8] and catalyst preparations [9] because it allows the flexible design of a microenvironment around the Abstract: The aerobic oxidative polymerization of phenol derivatives can provide poly(phenylene oxide)s, which are known as engineering plastics. This oxidation can be carried out with atmospheric oxygen molecules as the oxidizing reagent in the presence of copper complexes as the catalyst; however, stoichiometric or excess amounts of bases are also generally required.…”
Section: Introductionmentioning
confidence: 99%